2x-3x+18=-4x-4

Simple and best practice solution for 2x-3x+18=-4x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3x+18=-4x-4 equation:


Simplifying
2x + -3x + 18 = -4x + -4

Reorder the terms:
18 + 2x + -3x = -4x + -4

Combine like terms: 2x + -3x = -1x
18 + -1x = -4x + -4

Reorder the terms:
18 + -1x = -4 + -4x

Solving
18 + -1x = -4 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
18 + -1x + 4x = -4 + -4x + 4x

Combine like terms: -1x + 4x = 3x
18 + 3x = -4 + -4x + 4x

Combine like terms: -4x + 4x = 0
18 + 3x = -4 + 0
18 + 3x = -4

Add '-18' to each side of the equation.
18 + -18 + 3x = -4 + -18

Combine like terms: 18 + -18 = 0
0 + 3x = -4 + -18
3x = -4 + -18

Combine like terms: -4 + -18 = -22
3x = -22

Divide each side by '3'.
x = -7.333333333

Simplifying
x = -7.333333333

See similar equations:

| 4n+65=93 | | U=48n+210+7n+7 | | 18+2x=6y | | 1x+30=2x | | Y=2/9x-7 | | 1x+54=7x | | 2=10/3z=3z-7/3 | | 1/16a^2-1/25=0 | | a=8+b | | U=6*8n+6*35+7*n+7*1 | | =6*8n+6*35+7*n+7*1 | | x^2-208=0 | | f(a)=4x^2+2x+8 | | 2n+m-7m=-2 | | 5/6=-1/8x | | 1/3x2-4=21 | | 7x^2+6xy-y^2=0 | | 4(x+6)-3x=-2x+2-8 | | 0.7x-33.33=x+7 | | 11a-b+3a-(-7b)= | | w^2-3w-1890=0 | | 12x^2-(4x-3)(3x+1)=-2 | | 4(x-4)+2x=3(x-2)+5 | | 0.75x-33.3=x+7 | | U=23(6)+240 | | 3x-x=15 | | U=23n+240 | | 6x+9-7x-14=0 | | -3t(t-1)=2t+6 | | 2/2x-5/6x | | U=14n+9n+231+9 | | (8x^5)/(3)-(7x^3)/(6) |

Equations solver categories